2015
DOI: 10.1371/journal.pone.0139870
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary Delivery of Human Mesenchymal/Stromal Stem Cells: Insights from Coronary Microcirculation Invasive Assessment in a Swine Model

Abstract: BackgroundMesenchymal stem/stromal cells have unique properties favorable to their use in clinical practice and have been studied for cardiac repair. However, these cells are larger than coronary microvessels and there is controversy about the risk of embolization and microinfarctions, which could jeopardize the safety and efficacy of intracoronary route for their delivery. The index of microcirculatory resistance (IMR) is an invasive method for quantitatively assessing the coronary microcirculation status.Obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…Because retention of cells in the heart is calculated as a percentage of the total administered cell dose in case of in vivo analysis, it is probable that a higher cell dose would not result in a higher retention rate. However, it is known that infusion of larger volumes of cells (30×10 6 –50×10 6 ) via the IC route can result in a higher index of microcirculatory resistance 17 18…”
Section: Discussionmentioning
confidence: 99%
“…Because retention of cells in the heart is calculated as a percentage of the total administered cell dose in case of in vivo analysis, it is probable that a higher cell dose would not result in a higher retention rate. However, it is known that infusion of larger volumes of cells (30×10 6 –50×10 6 ) via the IC route can result in a higher index of microcirculatory resistance 17 18…”
Section: Discussionmentioning
confidence: 99%
“…Urethras (n = 17: female, n = 9 and male, n = 8) were obtained from cadaveric female Yorkshire piglets (Group 1: 8.2 ± 3.8 Kg, n = 11) and Duroc male and F1 Large White X Landrace pigs (Group 2: 31 ± 3.9 Kg, n = 6). Cadaveric animals were provided from experimental studies approved by the Animal Care and Use Committee (ACUC) of Wake Forest University Health Sciences in USA and Direcção Geral de Alimentação e Veterinária (DGAV) in Portugal 25 . Animal handling and dissections were performed in accordance with guidelines and regulations of ACUC and DGAV.…”
Section: Methodsmentioning
confidence: 99%
“…This approach could allow the cells to remain in the cardiac tissue long enough to adhere to endothelium and migrate into the extravascular space. Balloon occlusion could also provide enough transient ischemia to allow for a mild injury that would “condition” the local environment promoting donor cell survival and retention [8,9]. Another consideration is that only a subset of hMSCs retain long-term engraftment capability.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies support the ability of these MSCs either to repair or regenerate damaged myocardium [35], although their long-term durability in tissue is controversial [6,7]. The safety of MSC delivery to the left ventricle after acute myocardial infarction has also been established, via intracoronary, intramyocardial, or intravenous routes of administration [8,9]. Preclinical studies have also suggested that cell therapy with MSCs has substantial potential to treat right ventricular (RV) remodeling and dysfunction resulting from pulmonary hypertension (PH) and other diseases of the lung [10,11].…”
Section: Introductionmentioning
confidence: 99%